Biodiversity Informatics for Public Policy. The case of CONABIO in Mexico - Soberón, Jorge (Biodiversity Informatics, 2022)
In this work I present an overview of the development of the system of biodiversity information that was developed for the federal government of Mexico. I describe briefly the organization that made the system possible and some of its history. Then I focus on the principles of design of the information system, and a few of its major uses. I provide data on costs and usage, and finish reflecting on the institutional fragility of such systems.